Use of Molecular Genetic Methods for Investigation of Outbreaks of Enterovirus Infection in the Subjects of the Far Eastern Federal District - Butakova, L. V.; Trotsenko, O. E.; Sapega, E. Yu; Kotova, V. O.; Balakhontseva, L. A.; Zaitseva, T. A.; Kurganova, O. P. (Èpidemiologiâ i vakcinoprofilaktika (Online), 2016)
The results of molecular genetic studies of clinical samples taken from three foci of outbreaks of enterovirus infection, registered on the territory of Khabarovsk Krai and Amur Oblast from 2012 through 2013 were reported. Several strains of enteroviruses were obtained: strains of Coxsackie A-4 and Coxsackie A-16 from De-Kastri rural locality, strains of ECHO-6 from Ust’-Urikma (Amur Oblast) and strains of Coxsackie A-6 from Raichihisnsk (Amur Oblast). Use of molecular genetic methods for investigation of collective morbidity and outbreaks of enterovirus infection help to confirm the identity of enteroviruses, isolated from patients and to identify the imported cases of infection.